Kajian Keunggulan Komparatif dan Strategi Pengembangan Sapi di Sumatera Utara - Intan AL Thafunnisa Simanjuntak; Nanda Mailisa Meutia; Novita Novita; Nurmala Nurmala; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Although North Sumatra's cattle farms have enormous potential for development, there are still several issues that hinder productivity and efficiency. The comparative advantages and development strategies of cattle farming in the region are the subject of this study. The methods used include literature analysis and secondary data from various relevant sources. The results showed that, although local cattle have advantages in terms of adaptation to the environment, their productivity is lower than imported cattle such as Brahman Cross. Some of the factors that lead to low productivity include poor feed management, limited use of technology such as artificial insemination, and an ineffective marketing system. In addition, this study found that by improving the efficiency of agricultural waste as feed, cattle farming can thrive, the use of biogas and improved marketing systems through farmer cooperatives. Improving the competitiveness of cattle farming in North Sumatra can be achieved through the application of technology and local wisdom-based approaches. This research is expected to help in making policies and strategies to develop more efficient and sustainable cattle farming in the future.